Three-dimensional Movements of Pert and Ptotic Breasts (Journal of Fiber Bioengineering and Informatics, 2012)
This paper applies a new Breast Coordinate System to measure three-dimensional breast movements,relative to the thorax by eliminating the effects of body rotation, translation, bending and tilting duringactivities. Two-dimensional and three-dimensional breast movement trajectories of pert breasts andptotic breasts are presented and compared from four different perspectives in both the global and localcoordinate systems. The scatter plot of breast displacements against time in x, y and z coordinates werefitted by polynomial functions. The movement amplitude of the ptotic breast is larger than that of thepert breast in all directions. In a vertical direction, the ptotic breast velocity is greater than that of thepert breast one.
Keywords: Breast Motion; Movement Trajectories; Local Coordinate System